The influence of perceptions of usefulness, user ease, and security on interest in using fund e-wallet with e-trust as intervening variable - Mujiyana, Mujiyana; Damerianta, Sahni; Mukodim, Didin; Harmadi, Ashur; Indriyani, Indriyani (Technium Social Sciences Journal, 2022)
The use of Information Technology in the banking sector presents innovations in financial services that are practical, safe, fast, and offer many advantages. This innovation is certainly very useful during the COVID-19 pandemic. The purpose of this study is to determine the effect of perceived usefulness, perceived ease of use, and perceived security on interest in using Dana e-wallet through e-trust as an intervening variable. The type of research conducted by the researcher is associative research. The results showed that perceived usefulness, perceived convenience, and perceived security had a significant effect on e-trust. E-trust has an effect on interest in using e-wallet. Perceptions of benefits and security have an effect on interest in using e-wallet, while perceptions of convenience have a significant effect on interest in using funds through e-trust as an intervening variable.